Data-driven cluster analysis and external validation identify phenotypic subgroups in renin-independent aldosteronism with differential cardiovascular risk and therapeutic implications - Liu, Yuqing; Zhang, Zhiheng; Zhou, Haifeng; Yan, Yutong; Zhou, Mei; Wang, Cong; Gao, Maoting; Tao, Jun; Bao, Meiling; Yang, Tao; Sun, Min; Yang, Yuhong (Frontiers in Endocrinology, 2025)
BackgroundRenin-independent aldosterone secretion contributes to aldosteronism and heightened cardiovascular risk, but renin-independent aldosteronism is highly heterogenous. A refined classification may assist in identifying individuals with distinct cardiovascular risk profiles and guide individualized treatment strategies.MethodsUnsupervised hierarchical clustering was performed using 12 clinical parameters from patients with renin-independent aldosteronism in our registry cohort (n=404). The cluster centroids derived from the discovery cohort were fixed and applied to the Framingham Heart Study Third Generation cohort (n=417) for subject classification. The identified clusters were evaluated for their association with cardiovascular outcomes, assessed by echocardiographic parameters, serum biomarkers and cardiovascular event rates.ResultsThree replicable clusters of patients with renin-independent aldosteronism were identified. Patients in cluster 2 showed the most severe metabolic abnormalities with the highest lipid and glucose levels, while patients in cluster 3 displayed the highest aldosterone levels. Both clusters 2 and 3 showed elevated baseline blood pressure and left ventricular remodeling compared with cluster 1. Cluster 2 exhibited the highest risk of cardiovascular disease, chronic heart failure and atrial fibrillation, followed by cluster 3, which showed a higher incidence of cardiovascular disease compared with cluster 1.ConclusionsWe identified 3 subgroups with differing degrees of target organ damage and cardiovascular risk. Our findings establish metabolic dysfunction, rather than aldosterone excess, as a potential dominant cardiovascular risk driver in RIA patients, defining a new risk paradigm. Patients with renin-independent aldosteronism with metabolic dysfunction or high aldosterone levels may benefit from mineralocorticoid receptor antagonists with different priorities for metabolic and cardiovascular protection. This new refined classification may help tailor optimal treatment strategies for patients with heterogenous renin-independent aldosteronism.